Reduced expression of P120 catenin in cholangiocarcinoma correlated with tumor clinicopathologic parameters - Zhai, Bo; Yan, He-Xin; Liu, Shu-Qin; Chen, Lei; Wu, Meng-Chao; Wang, Hong-Yang (World journal of gastroenterology : WJG, 2008)
AIM： To investigate the relationship between the expression of P120 and the clinicopathologic parameters in intrahepatic cholangiocarcinoma （ICC）. METHODS： An immunohistochemical study of E-cadherin and P120 catenin was performed on 42 specimens of ICC with a Dako Envision kit. RESULTS： The expression of E-cadherin and P120 was reduced in 27 cases （64.3%） and 31 cases （73.8%）, respectively. Both E-cadherin and P120 expressions were significantly correlated with the tumor histological grade （χ^2 = 9.333, P = 009 and χ^= 11.71, P = 0.003）, TNM stage （χ^= 8.627, P = 0.035 and χ^= 13.123, P = 0.004）, intrahepatic metastasis （χ^= 7.292, P = 0.007 and χ^= 4.657, P = 0.041, respectively） and patients′ survival （χ^= 6.351, P = 0.002 and χ^= 4.023, P = 0.000, respectively）. In addition, the expression of P120 was in concordance with that of E-cadherin （χ^ = 13.797, P = 0.000）, indicating that the expression of P120 may be dependent on that of E-cadherin. Finally, only P120 expression was found to be an independent prognostic factor in Cox regression model （r = 0.088, P = 0.049）. CONCLUSION： Down-regulated expression of E-cadherin and P120 occurs frequently in ICC and contributes to the progression and development of tumor. Both of them may be valuable biologic markers for predicting tumor invasion, metastasis and patients′ survival, but only P120 is an independent prognostic factor for ICC.